Tertiarisation and globalisation of productive systems: comparative analysis - Yulia Melikhova; José Antonio Camacho Ballesta; Ivana Holubcova (European Regional Science Association (ERSA), 2012)
It is commonly known that the provision of services is currently carried out at a global level. Tertiary activities not only continuously increase their share in total employment and value added, but also in international trade and, as a consequence, in the processes of externationalisation and offshoring, characteristic of contemporary globalisation. These processes help enterprises, especially SMEs, get access to certain types of services which could not be provided internally, and thus increase their level of efficiency and consequently an overall degree of competitiveness of the regions, in which they operate. The objective of this work consists in an analysis of globalisation of services provision in several regions of the European Union (EU), from the perspective of their productive systems. We propose to focus the analysis on Slovakia and four Spanish autonomous regions (Aragón, Madrid, Valencia and Andalucía). What this selection of territories is due to? Slovakia is one of the European Union new member states, situated in the centre of Europe, the fact that could boost its participation in the general globalisation processes. The size of this country in terms of population and extension of its territory is comparable with the EU NUTS 2 regions. The mentioned Spanish regions are also NUTS 2 regions. They are similar to Slovakia in terms of population (Madrid, Valencia), territory (Aragón) or population density (Andalucía) and what is more important there are input-output tables available for these regions. The methodology we aim to apply is based on input-output tables which enable to appreciate a variety of intersectoral relations existing in the economy. After approaching the general situation using the globalization ratios (foreign direct investment and trade in services), by means of the input-output tables we will be able to calculate the level of tertiarization of economies using mostly direct and total effects (Camacho, 1999) and their difference (the degree of internationalization). Besides, input-output tables enable to appreciate the services share in the intermediate consumption of the whole economy and of its different branches; and the share of imported services within the total intermediate consumption. By means of the analysis proposed we aim not only to study the regional productive systems from the point of view of globalization of services provision but also to appreciate whether there are any similarities between Slovakia and Spanish regions. It could be interesting to find out if the role played by Bratislava is important enough so that the whole country would show resemblance to Madrid for example. Or otherwise it is more similar to more industrial regions of Aragón and Valencia or agriculture and tourism oriented Andalucía.
Keywords: 330